Managing Human Resources The New Normal - Potgieter, Ingrid L.; Ferreira, Nadia (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book volume crafts an exciting, original account on the changes and requirements on managing human resources within the context of the new normal. Chapters in this book report on current research on the key constructs and processes underlying the management of human resources, both on an organisational strategic level as well as an individual employee level. Chapters compare current research trends in terms of future potential directions for the management of human resources within the context of the new normal. The book also critically evaluates the relevance, applicability and utility of the research findings and theoretical premises in various classical, current and potential emerging issues for research and practice in the smart digital technological world of work for human resource management. This volume approaches the concept of managing human resources with the new normal working context from a number of different angles. The authors have categorized them as conceptualizing human resource management in the context of the new normal (Part I), the critical issues in understanding the dynamics of strategic human resources management (Part II), critical issues in understanding the impact of the new normal on the psychology of employees (Part III), and the impact of the new normal on individuals with special needs (Part IV). The book ends in Part V of the volume, with an integrated reflection and conclusion on emerging issues for research and practice. The primary audience for this book volume is advanced undergraduate and postgraduate students in human resource management, as well as scholars in both academic and new normal working contexts. Human resource management practitioners will also have an interest in this book volume.
1 Introductory Chapter: Conceptualising human resource management in the context of the new normal -- PART I: Critical issues in understanding the dynamics of strategic human resource management -- 2 Reinventing strategic human resource management -- 3 The COVID-19 pandemic: Managing unplanned change as the new normal in the workplace -- 4 Designing work for humans: A revised consumer experience-based approach towards people management practices -- 5 Novel tools and new challenges to HRM communicational practices (and the increasingly important social role of the manager) -- 6 The new normal: Managing virtual working from a human resources perspective -- 7 Remuneration in the new normal -- 8 Remuneration strategies in the new normal -- PART II: Critical issues in understanding the impact of the new normal on the psychology of employees -- 9 Wellbeing in a post-pandemic world: A psychological perspective -- 10 Working remotely in the new normal: towards a conceptual framework for managing employee wellbeing -- 11 Agile coping in the new normal post covid career space: does your cognitive orientation matter? -- 12 Employees' mental health promotion using peer support model in the new normal -- 13 Managing employees' career status in relations to organisational commitment and career adaptability -- 14 Humanizing workplaces and enabling abilities: An inclusive approach to the new normal (re-normalizing together) -- PART III: Impact of new normal on individuals with special needs -- 15 Context of digitalized employment for older adults with autism spectrum disorder in the new normal -- 16 Working with individuals with multiple sclerosis during the new normal -- 17 Human Resource Considerations for Supporting Employees with Neurological Disorders: Multiple Sclerosis and Spinal Cord Injury -- PART IV: Integration and Conclusion -- 18 Reflection on the impact of the new normal on the management of human resources.
Keywords: Psychology, Industrial; Personnel management; Industrial Psychology; Organizational Psychology; Work and Organizational Psychology; Human Resource Management